Safety of Combined Statin and Fibrate Therapy: Risks of Liver Injury and Acute Kidney Injury in a Cohort Study from the Shizuoka Kokuho Database - Yohei Sobukawa; Taichi Hatta; Daito Funaki; Eiji Nakatani (Adis, Springer Healthcare, 2024)
Abstract Introduction Statins and fibrates are important means of preventing cardiovascular diseases, particularly when administered in combination as part of various therapeutic strategies. In this study, we explored the risks associated with various combinations of these drugs. Objective We aimed to evaluate the risk of 1-year hospitalization with acute kidney injury, liver injury, pancreatitis, or rhabdomyolysis related to the concurrent administration of statins and fibrates. Methods We performed a retrospective cohort study using data from the Shizuoka Kokuho Database, focusing on patients prescribed statins, fibrates, or a combination. Four drug exposure patterns were evaluated: adding statins to fibrates (exposure 1), switching from fibrates to statins (exposure 2), adding fibrates to statins (exposure 3), and switching from statins to fibrates (exposure 4). Hospitalization for the specified conditions within 1 year was the outcome. Propensity score matching was used to create balanced cohorts for comparison. Results We studied 269,226 statin users and 16,282 fibrate users. After propensity score matching, there were 498 participants in the group of exposure 1, matched with 2988 in the fibrate-only group; 1180 in the group of exposure 2, matched with 7080 in the fibrate-only group; 1183 in group of exposure 3, matched with 11,830 in the statin only group; and 1356 in group of exposure 4, matched with 13,560 in the statin only group. The 1-year hospitalization rate with liver injury was higher in the group of exposure 1 than in the fibrate-only group (1.2% vs 0.3%, p < 0.01), in the group of exposure 2 than in the fibrate-only group (0.9% vs 0.3%, p < 0.01), and in the group of exposure 4 than in the statin-only group (0.6% vs 0.2%, p = 0.02). There was also a higher risk of 1-year hospitalization with acute kidney injury in group of exposure 1 than in the fibrate-only group (1.3% vs 0.3%, p = 0.01) but not in evaluations of exposure 2, 3, and 4. However, there were no differences in the risks of 1-year hospitalization with pancreatitis or rhabdomyolysis among the matched groups. Conclusions We have demonstrated higher risks of 1-year hospitalization with liver injury or acute kidney injury associated with the use of combinations of statins and fibrates. This underscores the need for a cautious approach to the prescribing of such drug combinations and the importance of monitoring patients for potential adverse events.